1967
DOI: 10.3181/00379727-124-31857
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vitamin B12 and Methionine on Levels of Folic Acid Compounds and Folate Enzymes in Rat Liver.

Abstract: The close relation between the functions of vitamins B12 and folic acid is best dwumen ted by biochemical deficiency symptoms which are common to both, such as the increased urinary excretion of formimino-glutaniic acid (FIGlu) ,t aminoimidazole-carbommide (AIC) and formate( 1-3). In (both deficiencies, dietary rnethionine dimidshes or even abolishes these symptoms (4-6). The action of methionine may be explained by its effect on the tissue distribution of folk acid coenzymes. Noronha and Silverman ( 7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

1969
1969
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 2 publications
5
24
0
Order By: Relevance
“…The growth rate under the latter conditions is maximal at a folic acid concentration of 0.1 mM, over 40-fold higher than the concentration in Eagle's minimal essential medium (23). Thus, supplementation with methionine markedly reduced the level of exogenous folic acid required by cultured cells, consistent with a similar effect of methionine observed in whole animals (16,17).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The growth rate under the latter conditions is maximal at a folic acid concentration of 0.1 mM, over 40-fold higher than the concentration in Eagle's minimal essential medium (23). Thus, supplementation with methionine markedly reduced the level of exogenous folic acid required by cultured cells, consistent with a similar effect of methionine observed in whole animals (16,17).…”
Section: Discussionsupporting
confidence: 71%
“…Analogous methyltransferase activity is widely distributed in rat tissues (11) and has been detected in various cultured mammalian cells (12)(13)(14)(15). Studies of the regulation of 5-methylTHF: homocysteine methyltransferase have shown that supplementation of a deficient diet with B12 elevates the methyltransferase activity in chicken (7) and rat (16) liver and that this activity increases still further when methionine is removed from a B1rcontaining diet (7,11,16).…”
mentioning
confidence: 99%
“…Katzen (33) has demonstrated that the synthesis of 5,10-methylene THFA reductase is severely repressed by methionine in bacteria, but Kutzback et al (28) found no such repression in rat liver by methionine. Methionine appears to have a regulatory role via the transmethylation reaction in the tissue distribution of folic acid coenzymes.…”
Section: Methodsmentioning
confidence: 99%
“…In animals maintained on a folate-deficient diet, McGuffin et al (31), have shown that there is a parallel reduction in liver and plasma folate levels compatible with a transport pathway between liver and tissue. The kinetics of folate in vitamin B12 deficiency also conform to this model (32)(33)(34) …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the amount of additional ['4CH3]H4PteGlu, recovered by the liver at 1 h was <1% (Table II) (Table I and II), demonstrate that this is not quantitatively important. Because less of the label returned from [14CH3]H4PteGlu, than from CH3H4[3H]PteGlu1, and the returning folate was a suitable substrate for polyglutamate formation, the folate congener must have been nonmethylated (31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%